2018
DOI: 10.1016/j.pec.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Informed and patient-centered decision-making in the primary care visits of African Americans with depression

Abstract: Strengthening partnerships between depressed African Americans and their clinicians may improve patient-engaged decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Results from a meta-analysis of patient preferences for psychiatric disorders reported that overwhelmingly patients prefer psychological treatment compared with pharmacologic treatment. 12 Hines and colleagues 13 compared audiotapes of postvisit surveys from patients and their clinicians. They found that only 9% of depression-related treatment decisions met the basic elements of informed decision making.…”
mentioning
confidence: 99%
“…Results from a meta-analysis of patient preferences for psychiatric disorders reported that overwhelmingly patients prefer psychological treatment compared with pharmacologic treatment. 12 Hines and colleagues 13 compared audiotapes of postvisit surveys from patients and their clinicians. They found that only 9% of depression-related treatment decisions met the basic elements of informed decision making.…”
mentioning
confidence: 99%
“…Previous research in depressive primary care patients similarly found that greater PIC significantly increased the probability of depression resolution, 19 whereas depressed patients report more positive perceptions of clinical care during highly patient-centred visits. 20 M-PICS was positively correlated with most domains of cardiac anxiety indicated by the CAQ, with the weak positive correlation between heart-focused attention and PIC reaching statistical significance ( r = 0.39; P = 0.02). This may suggest that greater involvement in care makes patients with HCM more likely to demonstrate symptoms of cardiac anxiety or that anxious patients may be motivated to maintain greater involvement in care.…”
Section: Discussionmentioning
confidence: 85%